Child Maltreatment and Substance Use in Emerging Adulthood: Internalizing and Externalizing Behaviors at the Transition to Adolescence as Indirect Pathways. (August 2022) - Olson, Anneke E.; Shenk, Chad E.; Noll, Jennie G.; Allen, Brian
One well-established outcome of child maltreatment is an increased likelihood of substance use in emerging adulthood. However, research identifying the indirect pathways that explain this relation is lacking, thereby limiting substance use prevention efforts for the child maltreatment population. The present study helped address this gap by accessing data from The Longitudinal Studies on Child Abuse and Neglect (LONGSCAN; n = 1, 136), a prospective cohort study of child maltreatment from birth through age eighteen. Internalizing and externalizing problems at age twelve were examined as indirect effects of the relation between child maltreatment prior to age four and substance use at age eighteen. A multiple mediator model tested the total and specific indirect effects of internalizing and externalizing concerns while controlling for demographic risk factors. Results demonstrated that the total indirect effect for internalizing and externalizing behaviors was statistically significant, Standardized Point Estimate = 0.01, 95% CI: 0.00-0.02. Examination of the specific indirect effects revealed that only externalizing behaviors constituted an indirect pathway, Standardized Point Estimate = 0.01, 95% CI: 0.00-0.03. These results suggest that externalizing behaviors at the transition to adolescence are important intervention targets for reducing the risk for substance use in emerging adulthood in the child maltreatment population.